Who is Reading the Texts in Nepalese ELT Classes? Teachers? Or Students? - Kshetree, Arun Kumar; Jyoti, Rameswar; KC, Kamala; Pokhrel, Prem Raj; Gyawali , Shiva Kumar (Kaladarpan कलादर्पण, 2025)
The present paper is a case analysis of four secondary level English teachers teaching in community schools and institutional schools of Butwal Sub-metropolitan city related to the teaching of English reading skills in our secondary schools. With the aim of finding out of the ways and attitudes of English teachers towards teaching English reading skills, the interview and class observation techniques were employed after developing an interview guideline and a class observation checklist. The purposively selected teachers expressed their views on different issues of teaching reading in the ELT classes. They presented many problems of teaching reading and suggested ways of making the teaching of reading skills more effective.The common points to improve they suggested include restructuring the curricula, incorporating the technology in teaching and learning of reading skills and selecting culturally relevant and useful texts for the students to read. They also recommended that the teaching of reading can not be improved until w e move away from the exam centered teaching of reading and if we cannot stop teachers from paraphrasing the texts to the students and not encouraging them to read the texts, we cannot expect any change in the ways of teaching English reading in Nepal.